The role of platelet-lymphocyte ratio and neutrophil-lymphocyte ratio in early gestational week in predicting missed abortion - Duran, Mehmet Nuri; Karacaer, Kübra Özkan; Kel, Serem; Demir, Bülent (International Journal of Research in Medical Sciences, 2022)
Background: The definition of abortion was made by the World Health Organization based on the weight of the pregnancy material or the duration of pregnancy. According to this expression, the expulsion of all or some of the pregnancy material weighing less than 500 grams or before the 20th week of pregnancy from the uterine cavity is called abortion. Platelet-lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR), which are among the inflammation parameters likely to be increased in abortion, were compared in groups that resulted in abortion and did not result in abortion. Methods: The study included 120 patients who had a diagnosis of <14 weeks of abortion and 120 healthy pregnant women who applied to the gynecology and obstetrics clinic of a tertiary care hospital between January 2018 and December 2021. Those who had a previous fetal heartbeat or intracavitary pregnancy and aborted before the 14th gestational week were included in the selection of the abortus group. Results: NLR and PLR were analyzed with ROC curve analysis. The area under the curve (AUC) for NLR was 0.498, with 95% confidence intervals (0.424-0.572), and was not statistically significant (p=0.38). The area under the curve (AUC) for PLR was 0.480 at 95% confidence intervals (0.406-0.557), and was not statistically significant (p=0.38). Conclusions: NLR and PLR ratios were similar in both groups. As a result of the present study, it was found that there were no significant differences between the abortion NLR and PLR values between the groups (p>0.05).